2022
DOI: 10.2147/dmso.s376292
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of miR-155 in Peripheral Blood and Wound Margin Tissue of Type 2 Diabetes Mellitus Patients Associated with Diabetic Foot Ulcer

Abstract: To investigate the correlations of miR-155 expression in the peripheral blood and wound margin tissue of patients with diabetic foot ulcer (DFU) and explore the clinical value of miR-155 as a potential biomarker for the diagnosis and treatment outcomes of DFU. Methods: Sixty newly diagnosed T2DM patients without DFU (T2DM group), 112 T2DM patients with DFU (DFU group), and 60 healthy controls (NC group) were included. MiR-155 levels in the peripheral blood and wound margin tissue were determined by quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…Additionally, there was no signi cant difference in miR-155 expression levels between the painful and nonpainful neuropathy subgroups. Other clinical studies have reported similar ndings [33] , wherein peripheral blood miR-155 expression was downregulated in patients with T2DM but signi cantly increased in patients with Diabetic Foot Ulcer (DFU), possibly linked to the ongoing in ammatory state in DFU. Chen J et al [34] reported that silencing miR-155 could improve sciatic nerve damage, enhance angiogenesis and alleviate in ammation in DPN rats.…”
Section: Discussionsupporting
confidence: 62%
“…Additionally, there was no signi cant difference in miR-155 expression levels between the painful and nonpainful neuropathy subgroups. Other clinical studies have reported similar ndings [33] , wherein peripheral blood miR-155 expression was downregulated in patients with T2DM but signi cantly increased in patients with Diabetic Foot Ulcer (DFU), possibly linked to the ongoing in ammatory state in DFU. Chen J et al [34] reported that silencing miR-155 could improve sciatic nerve damage, enhance angiogenesis and alleviate in ammation in DPN rats.…”
Section: Discussionsupporting
confidence: 62%
“…The PB sampling has a low trauma risk, and it is easy and convenient to determine miR-222-3p in PB. On that account, combining our study with previous studies, 20 , 39 we recommend detecting miR-222-3p expression in PB to predict the therapeutic outcome of DFU.…”
Section: Discussionsupporting
confidence: 60%
“…Ulcer healing after eight weeks referred to spontaneous complete wound closure after eight weeks of DFU treatment (100% re-epithelialization), and recorded 8 weeks after the treatment. 20 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of microRNAs have been implicated in pathological diabetic healing [ 50 , 51 , 52 , 53 , 54 , 55 ]. A recent study identified the enhanced expression of miR-155 in the peripheral blood of T2DM patients as a potential predictor for the onset of DFU [ 56 ], whereas the expression level of miR-203 in patients with DFU positively correlated with the severity of the damage [ 57 ]. A high expression level of miR-34c positively correlated with the amputation rates while negatively with the healing response and was also identified as an independent risk factor for ulceration and osteomyelitis [ 58 ].…”
Section: Introductionmentioning
confidence: 99%